INNOVATION CULTURE AND AMBIDEXTERITY: STRATEGIES TO DEAL WITH ENVIRONMENTAL UNCERTAINTY - Kumalaningrum, Maria Pampa; Wibowo, Bambang Setia (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aimed to investigate the role of exploration and exploitation ambidexterity as a mediating factor in the relationship between innovation culture and innovation performance. Additionally, environmental uncertainty was examined as a moderating factor in the interaction between ambidexterity and innovation performance. The research used an explanatory deductive approach, conducting a survey with a purposive sampling method involving 205 SMEs in the creative industries across Malang, Solo, Semarang, and Denpasar. Path analysis with ordinary least squares regression was used to test mediation and moderation effects. The findings revealed that the relationship between innovation culture and innovation performance is mediated by exploration and exploitation ambidexterity. The study also confirmed that the dynamic environment significantly moderates the impact of exploration on innovation performance. However, environmental uncertainty was not found to moderate the effect of exploitation on innovation performance. This research combines perspectives from resource-based theory and dynamic capabilities, offering valuable insights into the role of ambidexterity within SMEs.